2021
DOI: 10.3389/fpsyg.2021.640548
|View full text |Cite
|
Sign up to set email alerts
|

Face Masks Protect From Infection but May Impair Social Cognition in Older Adults and People With Dementia

Abstract: The coronavirus disease 2019 (COVID-19) pandemic will have a high impact on older adults and people with Alzheimer's disease and other dementias. Social cognition enables the understanding of another individual's feelings, intentions, desires and mental states, which is particularly important during the COVID-19 pandemic. To prevent further spread of the disease face masks have been recommended. Although justified for prevention of this potentially devastating disease, they partly cover the face and hamper emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…For instance, some studies already shown that wearing face mask reduces accuracy in emotion recognition and perceived closeness ( Grundmann et al, 2021 ) and that this effect is even larger for individuals with autistic traits ( Pazhoohi et al, 2021 ). Moreover, a reduction in accuracy when identifying emotions in masked vs. no-masked faces stimuli was also reported for a population, healthcare students, that is planned to be exposed to masked human faces in the next future ( Bani et al, 2021 ) and across the lifespan with older adults ( Schroeter et al, 2021 ), adults (e.g., Carbon, 2020 ), and children ( Ruba and Pollak, 2020 ) experiencing the same effect. While generally agreeing on the phenomenon, existing results in literature highlight some differences for what concerns the expressed emotion.…”
Section: Introductionmentioning
confidence: 68%
“…For instance, some studies already shown that wearing face mask reduces accuracy in emotion recognition and perceived closeness ( Grundmann et al, 2021 ) and that this effect is even larger for individuals with autistic traits ( Pazhoohi et al, 2021 ). Moreover, a reduction in accuracy when identifying emotions in masked vs. no-masked faces stimuli was also reported for a population, healthcare students, that is planned to be exposed to masked human faces in the next future ( Bani et al, 2021 ) and across the lifespan with older adults ( Schroeter et al, 2021 ), adults (e.g., Carbon, 2020 ), and children ( Ruba and Pollak, 2020 ) experiencing the same effect. While generally agreeing on the phenomenon, existing results in literature highlight some differences for what concerns the expressed emotion.…”
Section: Introductionmentioning
confidence: 68%
“…Mask wearing is perhaps unfamiliar protective behavior for U.S. older individuals. Schroeter et al (2021) discussed that mask wearing may impair recognition of emotions and interaction among people despite its justification for disease prevention. It is worse among older adults because they may have experienced some decline in social cognition ( Schroeter et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Schroeter et al (2021) discussed that mask wearing may impair recognition of emotions and interaction among people despite its justification for disease prevention. It is worse among older adults because they may have experienced some decline in social cognition ( Schroeter et al, 2021 ). But younger and agreeable individuals may be more likely to see the benefits of this health behavior, particularly since they are more likely to be mobile in their community.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, older people might lack expertise in exploring upper facial regions, which is necessary when the lower face is covered by a mask. Those changes in communication associated to face masking could even accelerate cognitive decline in the long run ( Schroeter et al ., 2021 ). As social cognition is already affected by aging and dementia, strategies have to be developed to cope with these profound changes in communication in older individuals.…”
Section: Impact Of Mask Wearing On Verbal and Nonverbal Communicationmentioning
confidence: 99%